Meningkatkan Aktivitas Belajar Siswa Melalui Model Pembelajaran Scientific Inquiry dalam Pembelajaran Matematika Kelas I SDN 4 Klambu, Kabupaten Grobogan - Jasti Wiyani (eductum: Jurnal Literasi Pendidikan, 2023)
This research is an action research utilizing a planning, action, observation, and reflection cycle. It originated from a teacher's initial reflection on December 6, 2022, which revealed low mathematics scores among 1st-grade students. Their first-semester test results averaged only 5.8, prompting the need for guidance according to educational guidelines (KKTP). To address this, the author introduced the scientific inquiry learning model in mathematics classes for 1st-grade students at SD Negeri 4 Klambu. The research aimed to (1) enhance student engagement and (2) improve learning outcomes using this model. It employed a qualitative descriptive approach, collecting data through test sheets to evaluate learning outcomes and observation sheets to measure student engagement. The research outcomes demonstrated increased student learning performance and active participation in learning activities through the scientific inquiry model. Consequently, it can be concluded that implementing the scientific inquiry learning model positively impacts student performance, particularly in exploring various concepts. These findings suggest that educators can consider this model as an effective and innovative approach for teaching and learning.